Testfishing in Örserumsviken 2000-2009 - Tobiasson, Stefan (Linnaeus University, 2019)
Biological data from coastal water generated in recipient control programs i Kalmar County inSweden.
The database consists of 13 tables. The data is generated from testfishing outside the pulpmill of Mönsterås.

Biologiska data från kustvatten som genereras i mottagarstyrningsprogram i Kalmar län i Sverige.
Databasen består av 13 tabeller. Uppgifterna genereras av provfiske utanför Mönsterås massakälla.
Provfiske i Örserumsviken 2000-2009
Keywords: coastal management; sustainable fisheries; Biological Systematics; Biologisk systematik; Biota; Biologi och ekologi